Analysis of the Impact of Globalization and Digitalization on Welfare in ASEAN and BRICS Countries - Bestari, Mohamad Fidelio Omar; Yusgiantoro, Inka Brahmantyo; Trihadmini, Nuning; Suhartoko, Yohanes Berchman (Yayasan Sinergi Kawula Muda, 2026)
This study investigates the multifaceted impacts of two global megatrends—globalization and digitalization—on public welfare in the ASEAN and BRICS nations from 2007 to 2024. Amid the prevailing narrative that links both phenomena to economic progress, this thesis critically analyses the influence of proxy variables for globalization (trade openness and foreign capital inflows) and digitalization (internet penetration and social media usage), alongside crucial domestic factors such as corruption and entrepreneurship, on three primary welfare indicators: per capita income, unemployment rate, and the poverty level. The principal objective of this research is to deliver nuanced empirical evidence on how the interplay of external forces and internal conditions shapes the welfare landscape in two of the world's most dynamic economic blocs. Employing a quantitative approach through panel data regression analysis, the findings reveal complex and non- uniform relationships. The analysis indicates that trade openness and internet penetration significantly contribute to a reduction in the unemployment rate. Conversely, social media usage demonstrates a negative correlation with per capita income and a positive association with rising poverty, suggesting potential counter-productive impacts and the promotion of consumptive behaviours. Furthermore, domestic governance factors, particularly corruption, are proven to have a significant influence on impeding income growth and exacerbating employment conditions. These findings affirm that the benefits of globalization and digitalization are not automatic but are heavily contingent upon the quality of domestic institutions and policies capable of optimizing opportunities and mitigating emergent risks.